2015
DOI: 10.1101/gad.267633.115
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin and IGF-1 signaling synchronize cell proliferation and maturation during erythropoiesis

Abstract: Tight coordination of cell proliferation and differentiation is central to red blood cell formation. Erythropoietin controls the proliferation and survival of red blood cell precursors, while variations in GATA-1/FOG-1 complex composition and concentrations drive their maturation. However, clear evidence of cross-talk between molecular pathways is lacking. Here, we show that erythropoietin activates AKT, which phosphorylates GATA-1 at Ser310, thereby increasing GATA-1 affinity for FOG-1. In turn, FOG-1 displac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…This finding corresponds to the size increase of the erythroid population during infection, annotated by the specific gene markers Gypa , Hbb-bt , and Tfrc ( Figures 4D, E ). Finally, it is worth mentioning that EBIM and TRM2 are increased for the gene encoding Insulin-like growth factor 1 ( Igf1 ) ( Figure 4C ), which has been reported to be produced by macrophages to promote erythroid cells proliferation ( 59 ). Hence, combined evidences indicates that T. evansi -induced TRMs and EBIMs all play a central role in infection-induced extramedullary erythropoiesis.…”
Section: Resultsmentioning
confidence: 99%
“…This finding corresponds to the size increase of the erythroid population during infection, annotated by the specific gene markers Gypa , Hbb-bt , and Tfrc ( Figures 4D, E ). Finally, it is worth mentioning that EBIM and TRM2 are increased for the gene encoding Insulin-like growth factor 1 ( Igf1 ) ( Figure 4C ), which has been reported to be produced by macrophages to promote erythroid cells proliferation ( 59 ). Hence, combined evidences indicates that T. evansi -induced TRMs and EBIMs all play a central role in infection-induced extramedullary erythropoiesis.…”
Section: Resultsmentioning
confidence: 99%
“…Mice harboring a Gata1 S310A mutation develop severe anemia when a compensatory pathway for EF-2 production (IGF1 signaling) is abolished. 21 Furthermore, our patient developed severe fetal anemia and manifested with persistent anisocytosis and elevated levels of HbF during childhood (39.7% HbF at birth; 6.7% at 5 years of age). Previous studies have shown that GATA1 plays a fundamental role in fetal globin gene expression (eg, gene silencing of HBG1 and HBG2 and hemoglobin switching to HBB is promoted by GATA1).…”
mentioning
confidence: 71%
“…The role of Ser310 phosphorylation for GATA1 affinity to FOG1 is historically controversial, depending on the experimental setup used. 21-24 Nevertheless, the clinical presentation of our patient with severe fetal anemia and thrombocytopenia and impaired maturation of the erythrocytes, combined with reduced phosphorylation resulting in impaired GATA1/FOG1 binding in R307H mutation, underlines the clinical relevance. Kadri et al showed that phosphorylation at Ser310 enhances the affinity of GATA1 for its cofactor, FOG1.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Moreover, scRNA-seq revealed that the expression levels of GATA2 and its coactivator friend of GATA-1 (FOG1) were relatively higher in Mk-HSCs (Figure 6B). GATA factors can be phosphorylated by Akt to increase its affinity for FOG1 (Kadri et al, 2015). GATA2 phosphorylation at Ser401 (Figure 6C) and GATA2/FOG1 association (Figure 6D) were enhanced (C and D) Frequency and CD41 expression of HSCs after 14-day culture in CM (0.9 mM Pi) and HPM (4 mM Pi) with or without soluble Klotho supplementation (n = 5).…”
Section: The Klotho-pi Axis Governs Akt Activity In Hscsmentioning
confidence: 99%